Synthesis and crystal structures of copper complexes with N, N, N-tridentate chelating ligands containing o-phenanthroline-appended benz-fused polyazoles and their catalytic application in A3 coupling reaction. (1st February 2023) - Pandey, Sharmila; Mandal, Tanmoy; Kumar Mandal, Sanajit
Graphical abstract: Two new copper complexes [Cu(L1 )2 (OClO3 )][ClO4 ] (Cu-1 ) and [Cu(L2 )(OClO3 )(OH2 )2 ][ClO4 ] (Cu-2 ) of N, N, N -tridentate chelating ligands containing o-phenanthroline-appended benz-fused poly-azoles were synthesized and characterized well via crystallographic and spectroscopic techniques. The complexes were used as efficient precatalysts in A 3 coupling reactions for the synthesis of propargylamines. Abstract: Design of two new N -enriched N, N, N -tridentate chelating ligands comprising of benz-fused polyazole-based heterocyclic scaffolds in combination with 1, 10-phenanthroline motif, has been presented in this work for exploring their Cu-complexes as structurally well-defined precatalysts for A 3 coupling reactions. With the two different tridentate N -donor ligands L1 and L2, two monomeric Cu(II) complexes, [Cu(L1 )2 (OClO3 )][ClO4 ] (Cu-1 ) and [Cu(L2 )(OClO3 )(OH2 )2 ][ClO4 ] (Cu-2 ) have been synthesized in good yield and characterized well with spectroscopic and crystallographic techniques. In spite of similar type of ligands, structures of the complexes are quite different which can be attributed to the electronic effect of the ligands. Crystal structure of Cu-1 reveals that the central copper ion is in octahedral geometry where one ligand is ligated in tridentate mode and the other is coordinated in a bidentate mode. In case of complex Cu-2, it is observed that only one ligand has been coordinated in tridentate mode. The N -heterocyclic backbone possesses key electronic properties such as good π-accepting/σ-donating property, and efficient charge sinks due to the presence of the extended π-conjugation, Accordingly, both the complexes have been found to be efficient precatalysts in A 3 coupling of aldehydes, amines, and alkynes for the synthesis of propargylamines.